The transmission of music into the human uterus and the response to music of the human fetus and neonate - Woodward, Sheila C (College of Music, 2020)
The aim of this study was to investigate whether music influences human life before birth. In order to determine the existence and character of music in the uterine acoustic environment, a study was conducted involving the insertion of a hydrophone through the cervix, next to the fetal head. The investigation was conducted on eight women in early labour. The average residual uterine sound of the eight subjects was measured at 65 dBA (A-weighted) re 20 µ.Pa in a 1 O KHz band, RMS averaged over 32-second records. Above this emerged the maternal voice, an external female voice and a male voice presented at approximately 65 dB (linear weighted). Pure tones between 50 Hz and 1 O KHz and orchestral music, all presented at 80 dB (linear weighted), were also shown to emerge above the residual uterine sound. Attenuation of external sound was observed to vary as a function of frequency, with less attenuation of lower frequencies. It was determined that the music was transmitted into the uterus without sufficient distortion to significantly alter the recognisable characteristics of the music. The fetal heart rate (FHA) response to a music stimulus (MS) and a vibroacoustic stimulus (VS) was measured in 40 subjects. Gestational age of the fetuses ranged from 32 to 42 weeks. The study included a control period with no acoustic stimulation; a period with the presentation of 5 music stimuli; and a period with the presentation of 5 vibroacoustic stimuli. A change in the FHA of 15 beats per minute or greater, lasting 15 seconds and occurring within 15 seconds of at least 2 of the 5 stimuli (or a tachycardia of greater than 15 beats per minute above the resting baseline, sustained for one minute or longer) was considered to be a positive response. The MS elicited a positive response in 35 of the fetuses (the 5 non-responses occurring in a period of low FHA variability) and all 40 fetuses responded to the VS (regardless of arousal state). In the third study, mothers attending childbirth education classes volunteered to listen to a prescribed music excerpt twice daily from the 34th week of pregnancy. Ten neonates (all clinically normal) were tested betw~en the 2nd and 5th day after birth. Investigators observed the effect of two music sti:Tiuli, the prescribed stimulus and a non-prescribed stimulus, on neonatal sucking of a non-nutritive nipple. A five-minute control period with no stimulation was compared with a ten-minute period during which two music stimuli were presented. By random allocation, either the prescribed music stimulus (PM) or the nonprescribed music (NM) was presented contingent upon sucking pressure. If a sucking burst was initiated, the PM stimulus was activated. On cessation of sucking, the NM stimulus was activated. Randomly, the procedure would be reversed for some of the subjects, where initiation of sucking activated the NM stimulus and cessation of sucking activated the PM stimulus. It was determined that the inter-burst intervals during the music period were significantly extended when coinciding with the PM stimulus and significantly shortened when coinciding with the NM stimulus.The studies indicated that music is transmitted into the uterus with insufficient distortion to alter the character of the music; that the normal fetus responds to a music stimulus from at least the 32nd week of gestation; and that the neonate alters the normal sucking pattern to activate longer periods of a music stimulus which has been repeatedly presented during the intrauterine stage and shorter periods of a novel music stimulus.